Pengaruh Persepi, Motivasi Dan Pengetahuan Perpajakan Terhadap Minat Berkarir Di Bidang Perpajakan - Panjaitan, Martha; Tobing, Vargo Christian L. (Peneliti.net, 2023)
This study aims to determine the effect of perception, motivation and knowledge of taxation on students' interest in a career in the field of taxation. This research was conducted at several universities in Batam City. The students who were used as the population were students majoring in Accounting for the 2021/2022 even period academic year, totaling 3,479 students. This research was distributed via google form to send a questionnaire survey as a way of collecting data. The sample collection technique used purposive sampling using the slovin formula with a significant level of 10% resulting in a sample of 100 respondents. Tests carried out in this study included validity and reliability tests, descriptive statistical analysis, classic assumption tests, namely the normality test, multicollinearity test and heteroscedasticity test, multiple linear regression tests and hypothesis testing, namely the T test, F test and determination analysis. The results of testing the hypothesis in this study stated that partially perception has a significant effect on student interest in a career in taxation, as well as motivation partially has a significant effect on student interest in a career in taxation, and knowledge of taxation partially has a significant effect on student interest in a career in taxation. Perception, motivation and knowledge of taxation simultaneously (together) have a significant effect on students' interest in a career in the field of taxation. The results of the coefficient of determination show that the variables of perception, motivation and knowledge of taxation have an influence of 72.2% on the variable of career interest in taxation, while the remaining 27.8% is influenced by other variables not included in the regression model.